New directions in corporate strategy - Twite, Garry; O'Keeffe, Michael (Allen and Unwin, 2000)
Introduction. Competition policy. Business strategy and industry policy. The triumph of the firm. Knowledge, tacit understanding and strategy. Corporate super-brands...